UV-induced conformational isomerization and photochemistry of 3-chloro-4-methoxybenzaldehyde in cryogenic inert matrices - Konarska, Jadwiga; Fausto, Rui; ILDIZ, GÜLCE ÖĞRÜÇ (AMER INST PHYSICS, 1305 WALT WHITMAN RD, STE 300, MELVILLE, NY 11747-4501 USA, 2019)
The interest in investigating the structure and reactivity of halogen- and methoxy-substituted benzaldehydes has been motivated by the practical relevance of these substances in various fields, from the fragrance industry to agrochemicals and drug manufacturing. In this study, 3-chloro-4-methoxybenzaldehyde (3CMBA) was investigated by matrix isolation infrared spectroscopy and quantum chemistry calculations. Molecules of the compound were isolated in cryogenic argon and xenon matrices and the conformational composition of the as-deposited materials characterized by infrared spectroscopy. Two nearly degenerated conformers, differing by the orientation of the aldehyde group relatively to the chlorine ring substituent, were successfully trapped into the matrices from the room temperature vapor of the compound, the cis conformer being slightly higher in energy than the trans form. Both conformers belong to the C-s point group and have the methoxy group pointing to the opposite direction of the chlorine atom. The as-deposited matrices of 3CMBA were then irradiated by tunable monochromatic UV-light. Irradiation within the 302-299 nm range induced conversion of the cis into the trans conformer, while irradiation in the 298-296 nm range induced the inverse photoisomerization. Irradiation at higher energy (250 nm) was found to lead to decarbonylation of both conformers. Very interestingly, the observed UV-induced processes were found to take place in an essentially selective way as a function of the irradiation wavelength. In particular, the conformational isomerization reactions of 3CMBA occur with only a residual number of molecules undergoing simultaneous decarbonylation.
Keywords: Molecular-Orbital Methods